Economic effiency of rain-fed rice production in Kayin State, Myanmar. Masters thesis - Nan, Wutyi San (2013)
The rice sector in Myanmar is predominantly for local consumption, maintaining national food security and uplifting the rural economy. The objectives of this study are to calculate the gross margin, examine the economic efficiency and then determine factors affecting efficiency of rice production in Kayin State. Data from a total sample of 400 rice farm households were collected using random sampling technique from two main growing areas in Kayin State. Results indicated that majority of farmers averaging 51 years old and had an average of 4 schooling years which treated agriculture as part time jobs. Farm experiences in paddy production were on average 22 years and average household’ family sizes were 6 members. However,family labors involved in farming were only 2 members while 86.5 % grew paddy on their own fields. In the study area, three kinds of paddy varieties were planted, on which, 17.75 % used traditional varieties, 60.25 % used HYV and the balance 22 % used new improved seeds. Out of the whole sample, 25% of farmers were access to extension services while 15.25% obtained farm loans from the credit institutions. With regard to fertilizer application,3.25% of samples had applied fertilizer in frequently. Average farm size were 3.01 ha and the observed average output was 2,205.72 kg/ha. Production costs were USD 376.47/ha and total revenue was USD 485.26/ha; therefore, the mean value of gross margin was USD 108.79/ha. Empirical results of efficiency analysis revealed that the mean pure technical efficiency,allocative efficiency, economic efficiency, overall technical efficiency and scale efficiency were 80.9 %, 66.8 %, 54.4 %, 50.6 % and 62.7%, respectively. About 2.25% of samples achieved the highest efficient level under constant returns to scale,another 97% operated under increasing returns to scale while 0.75 % operated under decreasing returns to scale. Efficiency analysis results showed that 38 DMUs or 9.50 % were the technically best practiced farms while 7 DMUs or 1.75 % were the allocatively and economically best practiced farms, thus they all were the benchmarks for other producers. The benefits from potential efficiency improvement revealed that total production costs would save by about USD 68.91/ha at fully pure technical efficiency, USD 125/ha at fully allocative efficiency and USD 167.90/ha at fully economic efficiency; therefore, the value of gross margin would increase to USD 177.70/ha at fully pure technical efficiency, USD 233.79/ha at fully allocative efficiency and USD 276.69/ha at fully economic efficiency. Major determinants on efficiency scores were age of farmers,education level, family sizes, access to extension services, farm sizes, frequency of fertilizer application and new improved seeds (seeds replacement). Thus, policies leading to improving farmers’ informal education levels, providing workshops and training programs are very important in order to sustain farm output. These will enhance the achievement of farms economic goals and increase farm efficiency in the area.